The Concept of Student Characteristics in the Perspective of Hadith - Muhammad Mamba'ul Mursidin, (Edumaspul: Jurnal Pendidikan, 2026)
Students have difficulties in the process of developing their potentials, all of which are caused by a lack of understanding of their characteristics, so that the learning and teaching process becomes less effective, innovative, and efficient. This study is expected to provide knowledge to readers about the many characteristics possessed by students, in addition to educating about the importance of understanding student characteristics in the teaching and learning process from the perspective of hadith. The method used in this study is qualitative with the type of library research. The data used in the study are sourced from the pole of al-sittah, Islamic Educational Philosophy towards character formation, individual differences in the learning process, the data processing process uses content analysis techniques (Content Analysis). The results of this study indicate that understanding characteristics is important for students in the process of developing and utilizing the potentials possessed by students. The development of students' potentials is influenced by the characteristics they get from two factors, the first is internal factors such as genes and given by Allah and the second is external factors in the form of social, cultural, and educational environmental influences. The benefits of understanding characteristics will also be felt by educators as a reference in the process of transferring knowledge to their students, so that the learning process becomes more effective and efficient. Abstrak Peserta didik memiliki kesulitan dalam proses pengembangan potensi-potensi yang dimilikinya, itu semua disebabkan oleh kurangnya pemahaman atas karakteristinya, sehingga proses belajar dan mengajar menjadi kurang efektif, inovatif, dan efisien. Penelitian ini diharapkan mampu memberi pengetahuan kepada pembaca mengenai banyaknya karakteristik yang dimiliki oleh peserta didik, selain itu juga mengedukasi mengenai pentingnya memahami karakteristik peserta didik dalam proses belajar mengajar dalam perspektif hadis. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan jenis penelitian library reshearch. Data yang digunakan dalam penelitian bersumber dari kutub al-sittah, Filsafat Pendidikan Islam menuju pembentukan karakter, perbedaan individu dalam proses pembelajara, proses pengolahan datanya menggunakan teknik analisis isi (Content Analysis). Hasil dari penelitian ini menunjukkan bahwa pemahaman karakteristik menjadi penting bagi peserta didik dalam proses pengembangan dan pemanfaatan potensi-potensi yang dimiliki oleh peserta didik. Perkembangan potensi-potensi yang dimiliki peserta didik dipengaruhi oleh karakteristik yang dia dapatkan dari dua faktor, yang pertama faktor internal seperti gen dan given Allah dan yang kedua faktor eksternal yang berupa pengaruh lingkungan sosial, budaya, dan pendidikan. Kemanfaatan pemahaman karakteristik juga akan dirasakan oleh pendidik sebagai acuan dalam proses transfer ilmu kepada peserta didiknya, sehingga dalam proses pembelajarannya menjadi lebih efektif dan efisien.